TACTICS OF TREATMENT OF GUNSHOT WOUNDS OF THE LIMB IN CONDITIONS OF MILITARY CITY SURGERY - Professor E.S. Djumabaev; Mirzaev K.K; Djumabaeva S.E; Saidkhodjaeva D.G; Pakirdinov A.S (Scholar Express Journals, 2022)
Optimization of tactics for the treatment of gunshot bullet wounds of the extremities in the conditions of military-urban surgery
Keywords: Military-urban surgery; gunshot wounds of extremities; regional lymphatic therapy